SISTEM PENGELOLAAN KAWASAN EKOWISATA DI PULAU TERNATE, MALUKU UTARA - , Muslim Fadel ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ecotourism is a form of special interest tourism activity that is a responsible travel to natural areas which conserve the environment and improve local peopleâs welfare by involving active participation of people nearby the area in form of sustainable management. This study focuses on management system of 3A (attractions, amenity, accessibility) and the promotion of ecotourism nearby Ternate Island. There are three sites of ecotourism observed. They are Batu Angus, Sulamadaha Beach, and Tolire Lake. The objectives of this study are: (1) To comprehend the management system of 3A (attractions, amenity, accessibility) and the promotion of ecotourism in the three sites (Batu Angus, Sulamadaha Beach, Tolire Lake) nearby Ternate Island. (2) To analyze the management system of 3A (attractions, amenity, accessibility) and the promotion of ecotourism in the three sites (Batu Angus, Sulamadaha Beach, Tolire Lake) located nearby Ternate Island. The method of research is conducted through survey and in-depth interviews using qualitative and quantitative approaches. The data used in this research consist of primary and secondary data. The primary data sources from observation, in-depth interviews, and direct documentation. Secondary data is derived from documentation analysis that relates to the geographical position, vast of area, climate, topography, and demography. The results of this study presents that the management system of 3A (attractions, amenity, accessibility) and the promotion of ecotourism in the three sites (Batu Angus, Sulamadaha Beach, Tolire Lake) have not been conducted optimally. It is caused by some factors such as limited human resources in the field of tourism, lack of funding, lack of cooperation among government, private and public sectors, as well as the lack of socialization on tourism awareness from Department of Culture and Tourism of Ternate that influence publicâs low awareness of tourism. Keywords: Management, Ecotourism, Ternate Island